Functional tape based on high-viscosity adhesive and preparation method thereof

By using high-viscosity adhesives, including acrylic monomers and high-temperature resistant crosslinking agents in the tape, the degumming problem caused by excessive temperature is solved, the adhesive performance and high-temperature resistant performance are improved, and the tape is given excellent waterproof performance and extended its service life.

CN118460128BActive Publication Date: 2025-03-28JIANGXI HAOZE OPTICAL FILM TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410707289.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-03
Publication Date
2025-03-28
Estimated Expiration
2044-06-03

AI Technical Summary

Technical Problem

During use, the tape is degummed, cracked, residual glue and other problems due to excessive temperature. Low viscosity leads to shedding, slipping, and damage, and has poor waterproof performance, which affects the use effect.

Method used

High-viscosity adhesives are used, including acrylic acid, hydroxyethyl acrylate, methyl methacrylate, glycidyl methacrylate, high-temperature resistant crosslinking agent and composite additives. Through crosslinking reaction and additive modification, the adhesive bonding performance, high-temperature resistance and waterproofing properties of the adhesive are improved.

Benefits of technology

It effectively avoids the degumming problem caused by excessive temperature of the tape, improves the bonding performance and high temperature resistance, extends the service life of the tape, and gives the tape excellent waterproof performance, avoids softening and loss of stickiness caused by water absorption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118460128B_ABST
    Figure CN118460128B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a functional adhesive tape based on a high-viscosity adhesive and a preparation method thereof. The functional adhesive tape comprises a substrate, a release agent and an adhesive respectively coated on both sides of the substrate; the adhesive comprises the following raw materials: acrylic acid, hydroxyethyl acrylate, methyl methacrylate, glycidyl methacrylate, a high-temperature resistant cross-linking agent, azobisisobutyronitrile, and a composite additive; wherein the high-temperature resistant cross-linking agent is prepared by grafting 3,4-dihydroxybenzoic acid into the structure of epoxy vinyl ester resin, so that the prepared adhesive tape has excellent high-temperature resistance and bonding performance; the composite additive is formed by chemically bonding K-type perfluoropolyether alcohol and curcumin, and after being added, the waterproof performance and antioxidant performance of the adhesive tape can be effectively improved, and the service life of the adhesive tape can be effectively extended.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a functional adhesive tape based on a high-viscosity adhesive and a preparation method thereof. Background Art

[0002] Adhesive tape is mainly composed of a substrate and an adhesive coated on the surface of the substrate. It is easy to stick and quick to use. It is widely used in the fields of automobiles, electronics, construction, home furnishings, packaging, and medical treatment. Adhesive is the most important component, which plays a bonding role. Through the adhesion and cohesion of the interface, two or more unconnected objects are connected together. Acrylic adhesive is an adhesive with acrylate as the main component. It has the advantages of good bonding performance, weather resistance, fast curing, high transparency, good flexibility and easy processing.

[0003] With the advancement of science and technology, people's requirements for product quality are also constantly improving. As a key component of connecting and fixing materials, the performance of tape directly affects the overall quality and reliability of the product. Therefore, the performance requirements for tape are getting higher and higher, that is, the performance requirements for the adhesive in the tape are also getting higher and higher. Unlike ordinary tapes, the adhesive in the tape used in emerging fields such as new energy, medical care, aerospace, etc. needs to withstand higher temperatures to avoid debonding, cracking, residual glue, etc. due to excessive temperature during use, which may damage the protected objects. At the same time, the adhesive in the tape needs to have excellent bonding properties to avoid the tape from falling off, slipping, and breaking due to viscosity failure, thereby extending the service life of the tape. In addition, the adhesive in the tape needs to have a certain waterproof performance. In the fields of packaging, construction, outdoor advertising, etc., if the adhesive is not waterproof, the tape will lose its viscosity, thereby affecting its use effect.

[0004] The invention patent with publication number CN105349072B discloses a high temperature resistant light-shielding adhesive composition and tape and preparation method. The invention prepares a high temperature resistant light-shielding adhesive composition with excellent high temperature resistance and good thermal stability and a high temperature resistant light-shielding tape using the high temperature resistant light-shielding adhesive composition by adding thermal conductive particles, black paste, isocyanate cross-linking agent and silane coupling agent to acrylic adhesive. Although the patent increases the direct contact area between thermal conductive particles by mixing boron nitride of different particle sizes, boron nitride particles of different particle sizes may interact or redistribute under long-term use or extreme conditions, affecting their performance. Based on this, it is of great significance for the present invention to develop a tape with excellent high temperature resistance, bonding performance and waterproof performance. Summary of the invention

[0005] The purpose of the present invention is to provide a functional adhesive tape based on a high-viscosity adhesive and a preparation method thereof, which solves the following technical problems:

[0006] (1) It solves the problems of debonding, cracking and residual adhesive caused by high temperature during the use of the tape.

[0007] (2) The problem of tape falling off, slipping, and breaking due to low adhesiveness was solved;

[0008] (3) The problem of poor waterproof performance of the tape has been solved.

[0009] The purpose of the present invention can be achieved through the following technical solutions:

[0010] A functional adhesive tape based on a high-viscosity adhesive comprises a substrate and a release agent and an adhesive respectively coated on both sides of the substrate; the adhesive comprises the following raw materials in parts by weight: 40 to 60 parts of acrylic acid, 20 to 30 parts of hydroxyethyl acrylate, 15 to 25 parts of methyl methacrylate, 8 to 12 parts of glycidyl methacrylate, 6 to 8 parts of a high-temperature resistant crosslinking agent, 0.5 to 1 part of azobisisobutyronitrile, and 4 to 6 parts of a composite additive.

[0011] Furthermore, the preparation method of the high temperature resistant cross-linking agent comprises the following steps:

[0012] Add epoxy vinyl ester resin and dimethyl sulfoxide solution into the reactor, stir mechanically, pass nitrogen for protection, add 3,4-dihydroxybenzoic acid and catalyst, raise the system temperature to 100-120°C under stirring conditions, keep warm for 5-7 hours, wait for the material to cool naturally, discharge the material, and obtain a high temperature resistant cross-linking agent.

[0013] Furthermore, the number average molecular weight of the epoxy vinyl ester resin is 2000-5000.

[0014] Furthermore, the catalyst is any one of trifluoromethanesulfonic acid, calcium methanesulfonate or tetrabutyl titanate.

[0015] Furthermore, the mass ratio of the epoxy vinyl ester resin to 3,4-dihydroxybenzoic acid is 1:0.1-0.3.

[0016] Through the above technical scheme, under the action of a catalyst, the hydroxyl group in the epoxy vinyl ester resin structure and the carboxyl group in the 3,4-dihydroxybenzoic acid structure react to form a high temperature resistant crosslinking agent containing a catechol structure and an alkenyl functional group in the structure.

[0017] Furthermore, the preparation method of the composite additive comprises the following steps:

[0018] A1: Add K-type perfluoropolyether alcohol to toluene solution, stir evenly, add bromoacetic acid and accelerator, pass nitrogen, exhaust air, turn on heating, maintain the temperature at 70-80°C, keep warm and stir for 2-3h, remove the solvent by rotary evaporation, and obtain the intermediate material;

[0019] A2: The intermediate material and N,N-dimethylformamide are added to a reactor filled with nitrogen in sequence, and after stirring evenly, curcumin and trifluoromethanesulfonic acid are added, and the temperature is raised to 105-115°C. After stirring at this temperature for 6-8 hours, the heating is stopped and the nitrogen is removed, and the temperature is lowered and the material is discharged to obtain a composite additive.

[0020] Furthermore, in step A1, the number average molecular weight of the K-type perfluoropolyether alcohol is 2000-3000.

[0021] Furthermore, in step A1, the promoter is any one of sodium carbonate or sodium bicarbonate.

[0022] Through the above technical scheme, under the action of the accelerator, the hydroxyl group in the K-type perfluoropolyether alcohol structure reacts with the halogen in the bromoacetic acid structure to introduce an active carboxyl group into the K-type perfluoropolyether alcohol structure to obtain an intermediate material. Under the action of trifluoromethanesulfonic acid, the carboxyl group in the intermediate material structure reacts with the hydroxyl group in the curcumin structure to obtain a composite additive.

[0023] A method for preparing a functional tape based on a high-viscosity adhesive comprises the following steps:

[0024] Step 1: Prepare adhesive

[0025] AA1: Add acrylic acid, hydroxyethyl acrylate, methyl methacrylate, glycidyl methacrylate and a high temperature resistant crosslinking agent into a reactor, stir mechanically to make them uniform, add azobisisobutyronitrile into the reactor under nitrogen protection, raise the system temperature to 50-70°C after adding, stir for 1-2h to obtain a premix;

[0026] AA2: Add the composite additive to the premix and stir at room temperature for 2 to 3 hours to obtain the adhesive;

[0027] Step 2: Prepare functional tape

[0028] (1) The release agent is evenly coated on one side of the substrate, and the substrate is placed in an oven at 70 to 90°C for curing for 10 to 15 minutes. After the curing, a release layer is obtained.

[0029] (2) The adhesive is evenly coated on the other side of the substrate, and the substrate is placed in an oven at 100 to 120°C for curing for 40 to 50 minutes. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

[0030] Furthermore, in step (1), the substrate is any one of a PET substrate, a PE substrate or a PTFE substrate.

[0031] Beneficial effects of the present invention:

[0032] (1) The present invention adopts 3,4-dihydroxybenzoic acid modified epoxy vinyl ester resin as a high temperature resistant crosslinking agent. In the polymerization process of acrylic acid, hydroxyethyl acrylate, methyl methacrylate, and glycidyl methacrylate monomers, they are crosslinked to obtain a premix. The molecular chains of the crosslinked premix present a crosslinked network structure with a large crosslinking density. On the one hand, it can make it have greater cohesion and improve the bonding performance of the adhesive. On the other hand, the high crosslinking density is conducive to limiting the movement of the molecular chains, so that the prepared adhesive has good high temperature resistance. In addition, the catechol structure in the high temperature resistant crosslinking agent structure further improves the bonding performance of the adhesive, so that the prepared adhesive tape has high viscosity. At the same time, the high temperature resistant crosslinking agent structure contains a rigid benzene ring and has high temperature resistance, which further enhances the heat resistance of the adhesive. Therefore, the high temperature resistance of the tape can be effectively improved, and the debonding, cracking, and residual adhesive of the tape due to excessively high temperature during use can be avoided, thereby extending the service life of the tape.

[0033] (2) The present invention prepares a composite additive as a filler modifier for the adhesive. On the one hand, the composite additive structure contains a large amount of CF bonds, which makes the prepared adhesive have a lower surface energy and is difficult to be wetted by water. Therefore, when it is applied to the tape, it can give the tape excellent waterproof performance, thereby effectively avoiding the problems of the tape becoming soft and losing its viscosity due to water absorption. On the other hand, the curcumin in the composite additive structure can effectively improve the antioxidant performance of the adhesive, thereby improving the antioxidant performance of the tape, preventing the tape from falling off due to oxidation, and effectively extending the service life of the tape. The improvement of these characteristics will greatly improve the application effect of the tape in various fields.

[0034] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0036] Figure 1 This is an infrared spectrum test chart of the epoxy vinyl ester resin and the high temperature resistant crosslinking agent prepared in Example 1 of the present invention.

[0037] Figure 2 This is an infrared spectrum test chart of the K-type perfluoropolyether alcohol, intermediate material and composite additive prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Example 1

[0040] 1. Preparation of high temperature resistant cross-linking agent

[0041] Add 10 g of epoxy vinyl ester resin with a number average molecular weight of 3000 and dimethyl sulfoxide solution into the reactor, stir mechanically, pass nitrogen protection, add 1.4 g of 3,4-dihydroxybenzoic acid and 0.1 g of trifluoromethanesulfonic acid, raise the system temperature to 110°C under stirring conditions, keep warm for 6 hours, wait for the material to cool naturally, discharge the material, and obtain a high temperature resistant cross-linking agent.

[0042] Bruker Vector22 Fourier transform infrared spectrometer was used to perform infrared characterization of epoxy vinyl ester resin and high temperature resistant crosslinking agent. The test results are shown in Figure 1 ,Depend on Figure 1 It can be seen that in the infrared spectrum of epoxy vinyl ester resin, 3024cm -1 The characteristic absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 1739 cm -1 The characteristic absorption peak of the ester group C=O appears at 3271cm -1 The characteristic absorption peak of hydroxyl group OH appears at 1025cm -1 The characteristic absorption peak of ether bond COC appears at 3005cm -1 The characteristic absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears at 1053 cm -1 The characteristic absorption peak of ether bond COC appears at 1758 cm -1 The characteristic absorption peak of the ester group C=O appears at the position, and the absorption peak of the ester group is enhanced.

[0043] 2. Preparation of composite additives

[0044] A1: Add 5 g of K-type perfluoropolyether alcohol with a number average molecular weight of 2800 to a toluene solution, stir evenly, add 0.8 g of bromoacetic acid and 0.05 g of sodium carbonate, pass nitrogen, exhaust air, turn on heating, maintain the temperature at 75°C, keep stirring for 2.5 hours, and remove the solvent by rotary evaporation to obtain an intermediate material;

[0045] A2: 5 g of the intermediate material and N,N-dimethylformamide were added to a reactor filled with nitrogen in sequence. After stirring evenly, 1.2 g of curcumin and 0.08 g of trifluoromethanesulfonic acid were added, and the temperature was raised to 110°C. After stirring at this temperature for 7 hours, the heating was stopped and the nitrogen was removed. The material was cooled and discharged to obtain a composite additive.

[0046] Bruker Vector22 Fourier transform infrared spectrometer was used to perform infrared characterization of K-type perfluoropolyether alcohol, intermediate material and composite additive. The test results are shown in Figure 2 ,Depend on Figure 2 It can be seen that in the infrared spectrum of K-type perfluoropolyether alcohol, 1235cm -1 The absorption peak of the CF bond in the trifluoromethyl group appears at 1076 cm -1 The absorption peak of ether bond COC appears at 3223 cm -1 The absorption peak of hydroxyl group OH appears at 1721m -1 The absorption peak of the carboxyl group C=O appears at 1040 cm -1 The absorption peak of ether-linked COC appears at 1762 cm -1 The characteristic absorption peak of the ester group C=O appears at 1020cm -1 The absorption peak of ether bond COC appears at 1718 cm -1 The characteristic absorption peak of carbonyl C=O in curcumin appears at 3074 cm -1 The absorption peak of the carbon-hydrogen bond in the carbon-carbon double bond appears, and the absorption peak of the carboxyl group disappears.

[0047] 3. Preparation of functional tape

[0048] Step 1: Prepare adhesive

[0049] AA1: 40 g acrylic acid, 20 g hydroxyethyl acrylate, 15 g methyl methacrylate, 8 g glycidyl methacrylate and 6 g high temperature resistant crosslinking agent were added to a reactor and mechanically stirred to be uniform. Under nitrogen protection, 0.5 g azobisisobutyronitrile was added to the reactor. After the addition, the system temperature was raised to 50°C and stirred for 1 hour to obtain a premix.

[0050] AA2: Add 4 g of the composite additive to the premix and stir at room temperature for 2 h to obtain the adhesive;

[0051] Step 2: Prepare functional tape

[0052] (1) The non-silicone release agent is evenly coated on one side of the PET substrate, and then placed in an oven at 70°C for curing for 10 minutes. After completion, a release layer is obtained;

[0053] (2) The adhesive is evenly coated on the other side of the PET substrate, which is placed in an oven at 100°C and cured for 40 minutes. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

[0054] Example 2

[0055] Preparation of functional tape

[0056] Step 1: Prepare adhesive

[0057] AA1: 50 g of acrylic acid, 25 g of hydroxyethyl acrylate, 20 g of methyl methacrylate, 10 g of glycidyl methacrylate and 7 g of a high temperature resistant crosslinking agent were added to a reactor and mechanically stirred to be uniform. Under nitrogen protection, 0.8 g of azobisisobutyronitrile was added to the reactor. After the addition, the system temperature was raised to 60°C and stirred for 1.5 hours to obtain a premix;

[0058] AA2: Add 5 g of the composite additive to the premix and stir at room temperature for 2.5 h to obtain the adhesive;

[0059] Step 2: Prepare functional tape

[0060] (1) The non-silicone release agent is evenly coated on one side of the PET substrate, and then placed in an oven at 80°C for curing for 12 minutes. After completion, a release layer is obtained;

[0061] (2) The adhesive is evenly coated on the other side of the PET substrate and placed in an oven at 110°C for curing for 45 minutes. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

[0062] The preparation method of the high temperature resistant crosslinking agent and the composite additive is the same as that in Example 1.

[0063] Example 3

[0064] Preparation of functional tape

[0065] Step 1: Prepare adhesive

[0066] AA1: 60 g of acrylic acid, 30 g of hydroxyethyl acrylate, 25 g of methyl methacrylate, 12 g of glycidyl methacrylate and 8 g of a high temperature resistant crosslinking agent were added to a reactor and mechanically stirred to be uniform. Under nitrogen protection, 1 g of azobisisobutyronitrile was added to the reactor. After the addition, the system temperature was raised to 70°C and stirred for 2 h to obtain a premix.

[0067] AA2: Add 6 g of the composite additive to the premix and stir at room temperature for 3 h to obtain the adhesive;

[0068] Step 2: Prepare functional tape

[0069] (1) The non-silicone release agent is evenly coated on one side of the PET substrate, and then placed in an oven at 90°C for curing for 15 minutes. After completion, a release layer is obtained;

[0070] (2) The adhesive is evenly coated on the other side of the PET substrate and placed in an oven at 120°C for curing for 50 min. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

[0071] The preparation method of the high temperature resistant crosslinking agent and the composite additive is the same as that in Example 1.

[0072] Comparative Example 1

[0073] Preparation of functional tape

[0074] Step 1: Prepare adhesive

[0075] 50g of acrylic acid, 25g of hydroxyethyl acrylate, 20g of methyl methacrylate, 10g of glycidyl methacrylate and 7g of a high temperature resistant crosslinking agent were added to a reactor and mechanically stirred to be uniform. Under nitrogen protection, 0.8g of azobisisobutyronitrile was added to the reactor. After the addition, the system temperature was raised to 60°C and stirred for 1.5h to obtain an adhesive.

[0076] Step 2: Prepare functional tape

[0077] (1) The non-silicone release agent is evenly coated on one side of the PET substrate, and then placed in an oven at 80°C for curing for 12 minutes. After completion, a release layer is obtained;

[0078] (2) The adhesive is evenly coated on the other side of the PET substrate and placed in an oven at 110°C for curing for 45 minutes. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

[0079] The preparation method of the high temperature resistant cross-linking agent is the same as that in Example 1.

[0080] Comparative Example 2

[0081] Preparation of functional tape

[0082] Step 1: Prepare adhesive

[0083] AA1: 50 g of acrylic acid, 25 g of hydroxyethyl acrylate, 20 g of methyl methacrylate, and 10 g of glycidyl methacrylate were added to a reactor and mechanically stirred to be uniform. Under nitrogen protection, 0.8 g of azobisisobutyronitrile was added to the reactor. After the addition, the system temperature was raised to 60°C and stirred for 1.5 h to obtain a premix;

[0084] AA2: Add 5 g of the composite additive to the premix and stir at room temperature for 2.5 h to obtain the adhesive;

[0085] Step 2: Prepare functional tape

[0086] (1) The non-silicone release agent is evenly coated on one side of the PET substrate, and then placed in an oven at 80°C for curing for 12 minutes. After completion, a release layer is obtained;

[0087] (2) The adhesive is evenly coated on the other side of the PET substrate and placed in an oven at 110°C for curing for 45 minutes. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

[0088] The preparation method of the composite additive is the same as that in Example 1.

[0089] Comparative Example 3

[0090] Preparation of functional tape

[0091] Step 1: Prepare adhesive

[0092] 50 g of acrylic acid, 25 g of hydroxyethyl acrylate, 20 g of methyl methacrylate, and 10 g of glycidyl methacrylate were added to the reactor and mechanically stirred to be uniform. Under nitrogen protection, 0.8 g of azobisisobutyronitrile was added to the reactor. After the addition, the system temperature was raised to 60°C and stirred for 1.5 hours to obtain an adhesive.

[0093] Step 2: Prepare functional tape

[0094] (1) The non-silicone release agent is evenly coated on one side of the PET substrate, and then placed in an oven at 80°C for curing for 12 minutes. After completion, a release layer is obtained;

[0095] (2) The adhesive is evenly coated on the other side of the PET substrate and placed in an oven at 110°C for curing for 45 minutes. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

[0096] Performance Testing

[0097] The functional adhesive tapes prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were cut into blocks that met the specifications and pasted on standard steel plates to prepare samples. According to GB / T 2792-2014 "Test Method for Peel Strength of Adhesive Tapes", the samples and the samples treated in a constant temperature box at 150°C for 24 hours were subjected to 180° peel strength tests to evaluate the high temperature resistance of the samples; according to GB / T 4852-2002 "Test Method for Initial Adhesion of Pressure-Sensitive Adhesive Tapes (Rolling Ball Method)", the samples were subjected to initial adhesion tests to evaluate the bonding properties of the samples; the samples were placed in an oven at 100°C for 48 hours, the degree of curling of the sample surface was observed, and the antioxidant properties of the samples were evaluated; the samples were subjected to water contact angle tests using a JC2000D2G contact angle tester to evaluate the waterproof properties of the samples. The specific test results are shown in the following table:

[0098] As can be seen from the above table, the samples prepared in Examples 1 to 3 all have excellent high temperature resistance, bonding performance, waterproof performance and antioxidant performance; in the sample prepared in Comparative Example 1, no composite additive is used as a modifier, and compared with the embodiment, the waterproof performance and antioxidant performance of the sample are poor, but a high temperature resistant cross-linking agent is added thereto, so the sample has good high temperature resistance and bonding performance; in the sample prepared in Comparative Example 2, no high temperature resistant cross-linking agent is added, so the cross-linking degree of the adhesive is low, resulting in a decrease in the high temperature resistance and bonding performance of the sample, but a composite additive is added thereto, so strong waterproof performance and antioxidant performance are maintained; in the sample prepared in Comparative Example 3, no composite additive and high temperature resistant cross-linking agent are added, so the performance of the sample is the worst.

[0099] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A functional tape based on a high-viscosity adhesive, characterized in that: It comprises a substrate and a release agent and an adhesive respectively coated on both sides of the substrate; the adhesive comprises the following raw materials in parts by weight: 40 to 60 parts of acrylic acid, 20 to 30 parts of hydroxyethyl acrylate, 15 to 25 parts of methyl methacrylate, 8 to 12 parts of glycidyl methacrylate, 6 to 8 parts of a high temperature resistant crosslinking agent, 0.5 to 1 part of azobisisobutyronitrile, and 4 to 6 parts of a composite additive; The preparation method of the high temperature resistant cross-linking agent comprises the following steps: Add epoxy vinyl ester resin and dimethyl sulfoxide solution into the reactor, stir mechanically, pass nitrogen protection, add 3,4-dihydroxybenzoic acid and catalyst, raise the system temperature to 100-120°C under stirring conditions, keep warm for 5-7 hours, wait for the material to cool naturally, discharge the material, and obtain a high temperature resistant crosslinking agent; The preparation method of the composite additive comprises the following steps: A1: Add K-type perfluoropolyether alcohol to toluene solution, stir evenly, add bromoacetic acid and accelerator, pass nitrogen, exhaust air, turn on heating, maintain the temperature at 70-80°C, keep warm and stir for 2-3h, remove the solvent by rotary evaporation, and obtain the intermediate material; A2: The intermediate material and N,N-dimethylformamide are added to a reactor filled with nitrogen in sequence, and after stirring evenly, curcumin and trifluoromethanesulfonic acid are added, and the temperature is raised to 105-115°C. After stirring at this temperature for 6-8 hours, the heating is stopped and the nitrogen is removed, and the temperature is lowered and the material is discharged to obtain a composite additive.

2. The functional tape based on a high-viscosity adhesive according to claim 1, characterized in that: The number average molecular weight of the epoxy vinyl ester resin is 2000-5000.

3. The functional tape based on a high-viscosity adhesive according to claim 1, characterized in that: The catalyst is any one of trifluoromethanesulfonic acid, calcium methanesulfonate or tetrabutyl titanate.

4. The functional tape based on a high-viscosity adhesive according to claim 1, characterized in that: The mass ratio of the epoxy vinyl ester resin to 3,4-dihydroxybenzoic acid is 1:0.1-0.

3.

5. The functional tape based on a high-viscosity adhesive according to claim 1, characterized in that: In step A1, the number average molecular weight of the K-type perfluoropolyether alcohol is 2000-3000.

6. The functional tape based on a high-viscosity adhesive according to claim 1, characterized in that: In step A1, the accelerator is any one of sodium carbonate or sodium bicarbonate.

7. A method for preparing a functional tape based on a high-viscosity adhesive as claimed in claim 1, characterized in that: The following steps are involved: Step 1: Prepare adhesive AA1: Add acrylic acid, hydroxyethyl acrylate, methyl methacrylate, glycidyl methacrylate and a high temperature resistant crosslinking agent into a reactor, stir mechanically to make them uniform, add azobisisobutyronitrile into the reactor under nitrogen protection, raise the system temperature to 50-70°C after adding, stir for 1-2h to obtain a premix; AA2: Add the composite additive to the premix and stir at room temperature for 2 to 3 hours to obtain the adhesive; Step 2: Prepare functional tape (1) The release agent is evenly coated on one side of the substrate, and the substrate is placed in an oven at 70 to 90°C for curing for 10 to 15 minutes. After the curing, a release layer is obtained. (2) The adhesive is evenly coated on the other side of the substrate, and the substrate is placed in an oven at 100 to 120°C for curing for 40 to 50 minutes. After completion, an adhesive layer is obtained. After cooling, winding, and cutting, a functional tape is obtained.

8. The method for preparing a functional tape based on a high-viscosity adhesive according to claim 7, characterized in that: In step (1), the substrate is any one of a PET substrate, a PE substrate or a PTFE substrate.

Citation Information

Patent Citations

  • A high-temperature resistant light-shielding adhesive composition and tape, and its preparation method

    CN105349072B

  • High temperature resistant pressure sensitive adhesive composition and preparation method thereof as well as double-sided adhesive tape

    CN103788901A

  • Acrylic acid pressure-sensitive adhesive tape and preparation method thereof

    CN115505350A